THE EFFECT OF SELF-EFFICACY AND HARDINESS ON BURNOUT IN NURSES - Natasya, Putri Silvia; Ika Mariyati, Lely; Asmara, Winda (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aimed to examine the relationship between self-efficacy, hardiness, and burnout among nurses, considering burnout as a psychological response to prolonged occupational stress. Method: Utilizing a correlational quantitative design, the study involved 161 nurses selected through random sampling from a population of 300. Data were collected using validated psychological scales: a self-efficacy scale (38 items, α = 0.829), a hardiness scale (16 items, α = 0.820), and a burnout scale (32 items, α = 0.973). Data analysis was conducted using multiple linear regression via IBM SPSS 30.0. Results: The analysis revealed a significant joint influence of self-efficacy and hardiness on burnout (F(3.00) = 62.778; p < .001). Furthermore, partial tests indicated that both self-efficacy (t = -8.609, p < .001) and hardiness (t = -2.900, p = .004) had significant negative effects on burnout, suggesting that higher levels of these psychological traits are associated with lower levels of burnout. Novelty: This study contributes to the field by empirically demonstrating the protective roles of self-efficacy and hardiness against burnout in healthcare professionals, offering evidence-based insights for psychological resilience-building interventions in high-stress clinical environments.